Initial Experience and Results of Combined Treatment for Atrial Fibrillation: Catheter Ablation with High-Power Short Duration Ablation and Left Atrial Appendage Closure - Vassallo, Fabricio; Serpa, Eduardo; Walker, Betina Reseck; Meigre, Lucas Luis; Carloni, Hermes; Simões Jr, Aloyr; Cunha, Christiano; Pezzin, Flávia; Loureiro, Karla; Amaral, Dalton; et al. (JOURNAL OF CARDIAC ARRHYTHMIAS, 2021)
Introduction: Long-term freedom from atrial fibrillation (AF) after catheter ablation and, consequently, the potential for stroke reduction remain unpredictable. Recently, left atrial appendage closure (LAAC) became an effective mechanical alternative to oral anticoagulation (OAC) for stroke prevention in AF patients. Objective: This study aims to evaluate the feasibility and safety of combined treatment for AF with catheter ablation (CA) with the high-power short duration technique associated with LAAC in one single procedure. Methods: Patients with non-valvular AF who underwent combined CA and LAAC procedure were included in the retrospective observational study. Between April 2018 and October 2020, 13 patients with AF were included, eight (61,54%) males, eight (61.54%) with persistent AF (PersAF), mean age 68.54 (65–84) years old, mean time from AF diagnosis to treatment 13.08 (3–33) months, mean CHA2VASC2 5.08 (3–7), all patients with coronary or vascular disease, 12 (92.31%) with hypertension, five (38.46%) with left ventricular dysfunction, four (30.77%) prior strokes using OAC and four (30.77%) patients with diabetes. Indications for LAAC included history of contraindication to OAC because of severe bleeding in eight (61.54%), previous stroke in four (30.77%) and two (13.08%) patients with LAA thrombus, despite the use of two different OAC (one associated with bleeding). One patient had a pseudoaneurysm in femoral artery, and two patients died of non-procedure complications after 30 days. At six months, angiotomography showed successful complete sealing of the LAA in seven (77.72%) of nine patients evaluated, and the two patients without it had a leak of less than 2 mm. After mean follow-up of 14 months (five to 33), 10 (90.91%) of the 11 patients were in sinus rhythm. Three (27.27%) patients, one in blanking period, recovered sinus rhythm after amiodarone. No cardioembolic or bleeding events occurred. Conclusion: In this small observational study, we showed the feasibility and safety of the combined therapy with AF catheter ablation with LAAC with a high rate of sinus rhythm and no cardioembolic event.